2020
DOI: 10.1111/hae.13928
|View full text |Cite
|
Sign up to set email alerts
|

Current state of play regarding dental extractions in patients with haemophilia: Consensus or evidence‐based practice? A review of the literature

Abstract: Due to the global prevalence of oral disease, tooth extraction is the most common surgical procedure required in general population thus likely to be similarly common in patients with haemophilia, especially those in older age and those living in countries with restricted resources. There are little or no consensus about optimal level and duration of factor replacement (FRP) therapy required to prevent bleeding complication following surgery and low levels of evidence to inform protocols and guidelines. The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…A recent review of the literature assessing rates of bleeding complications during and after oral surgery, particularly tooth extractions in PWH, reported similar bleeding rates with both pre-and postoperative factor replacement versus a single infusion of preoperative factor. 34 In our centre, PWHB routinely receive a single rFIXFc infusion prior to invasive dental surgery, tranexamic acid for 5 days postoperatively, and this approach, alongside local haemostatic measures, allows CFC consumption to be minimised. Factor replacement is only routinely used for dental extractions and not required for non-invasive dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the literature assessing rates of bleeding complications during and after oral surgery, particularly tooth extractions in PWH, reported similar bleeding rates with both pre-and postoperative factor replacement versus a single infusion of preoperative factor. 34 In our centre, PWHB routinely receive a single rFIXFc infusion prior to invasive dental surgery, tranexamic acid for 5 days postoperatively, and this approach, alongside local haemostatic measures, allows CFC consumption to be minimised. Factor replacement is only routinely used for dental extractions and not required for non-invasive dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Even though different national and international protocols and programs have considered dental treatment of children with hemophilia, there are still no strict recommendations or absolute statements in dental guidelines for Bulgaria. It may be because most studies showed diverse attitudes of medical and dental professionals to the treatment approach regarding this topic [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the readily available expertise in dental care has likely allowed a predating low bleeding rate and favourable outcomes before protocol implementation, as we did not find any major bleed either before or after protocol implementation and our post-procedural bleeding was comparable to or lower than reported bleeding rates in other cohorts of patients with haemophilia, von Willebrand disease and other bleeding disorders. 6,7,18 Alternatively, non-compliance to the protocol may have limited its effect and affected the outcomes in those patients. Lastly, as the baseline bleeding rate was low and given the rarity of inherited bleeding disorders, our study might lack the statistical power to detect a small difference in post-procedural bleeding rate between both groups.…”
Section: Discussionmentioning
confidence: 99%